2007
DOI: 10.1080/14622200601078277
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to nicotine: How the animal literature might inform future human research

Abstract: Despite a rich neuroscience literature on sensitization, this phenomenon has been neglected in clinical nicotine research. This paper offers a primer on the neuroscience of nicotine sensitization for behavioral scientists, identifying key concepts, potential theoretical and clinical implications, and directions for future research. Sensitization to a drug occurs when repeated exposures to the same dose produce greater responses. In animals, sensitization to nicotine, morphine, alcohol, cocaine, amphetamine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 0 publications
8
65
0
1
Order By: Relevance
“…Previous studies have reported attenuation of acute nicotine-induced locomotor activity (as distinct from sensitization) after passive immunization with a polyclonal anti-nicotine antiserum (Pentel et al, 2000), and vaccination or passive immunization with a monoclonal antibody (Carrera et al, 2004). The current study extends these data to LMS, a behavior mediated by pathways that overlap substantially with those mediating drug reinforcement and that is relevant to addiction treatment (DiFranza and Wellman, 2007). The data show that both vaccination alone and passive immunization alone are effective in attenuating LMS to nicotine, and they suggest that the pharmacokinetic and behavioral effects of immunotherapy depend on the total antibody concentration rather than their source (endogenously produced after vaccination or passively administered).…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have reported attenuation of acute nicotine-induced locomotor activity (as distinct from sensitization) after passive immunization with a polyclonal anti-nicotine antiserum (Pentel et al, 2000), and vaccination or passive immunization with a monoclonal antibody (Carrera et al, 2004). The current study extends these data to LMS, a behavior mediated by pathways that overlap substantially with those mediating drug reinforcement and that is relevant to addiction treatment (DiFranza and Wellman, 2007). The data show that both vaccination alone and passive immunization alone are effective in attenuating LMS to nicotine, and they suggest that the pharmacokinetic and behavioral effects of immunotherapy depend on the total antibody concentration rather than their source (endogenously produced after vaccination or passively administered).…”
Section: Discussionsupporting
confidence: 65%
“…The agonism of a7 and a4b2 nAChR subtypes can be among the Nic-mediated changes we observed here. In fact, chronic Nic exposure may trigger a cascade of events involving nicotinic receptor desensitization followed by long-lasting up-regulation (Gould and Leach, 2014;Markou, 2008;Dani and Bertrand, 2007;DiFranza and Wellman, 2007). We suggest that these processes could compensate for the disrupted cholinergic transmis- sion in icv-STZ, thus ameliorating mnemonic and synaptic plasticity deficits.…”
Section: Discussionmentioning
confidence: 87%
“…86 The rationale behind smoking cessation in HF is that nicotine has vasoconstrictor and proinflammatory activity. 87,88 Smoking cessation has been shown to reduce adverse outcomes and decrease mortality in HF, 89 yet a surprising number of people with HF continue to smoke. In a recent survey of 3778 German adults with a smoking history, more than half (52%) of those with a circulatory disorder, including HF, were current smokers.…”
Section: Smoking Cessationmentioning
confidence: 99%